Decoding Complexity Uncovering Patterns in Economic Networks - Glattfelder, James B.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Today it appears that we understand more about the universe than about our interconnected socio-economic world. In order to uncover organizational structures and novel features in these systems, we present the first comprehensive complex systems analysis of real-world ownership networks. This effort lies at the interface between the realms of economics and the emerging field loosely referred to as complexity science. The structure of global economic power is reflected in the network of ownership ties of companies and the analysis of such ownership networks has possible implications for market competition and financial stability. Thus this work presents powerful new tools for the study of economic and corporate networks that are only just beginning to attract the attention of scholars.
The Main Methodology: Computing Control in Ownership Networks -- Backbone of Complex Networks of Corporations: The Flow of Control -- The Network of Global Corporate Control -- The Bow-Tie Model of Ownership Networks.
Keywords: Physics; Mathematics; Engineering; Economics; Physics; Complex Networks; Economic Theory; Game Theory, Economics, Social and Behav. Sciences; Complex Systems; Complexity